Developing an Integrated Tax Administration Module Based on Latest Regulations to Improve Accounting and Finance Vocational High School Students' Understanding - Danik Indriastuti Surya Ningrum; Tri Rijanto; Ulil Hartono; Yessy Yessy; Heru Arizal (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Tax regulations in Indonesia have experienced dynamic developments since the enactment of the Law on Harmonization of Tax Regulations (UU HPP). This condition necessitates the availability of up-to-date teaching materials in Vocational High Schools (SMK) for the Accounting and Institutional Finance Skill Program. This study aims to develop a Tax Administration learning module integrated with the latest regulations and to analyze its feasibility, practicality, and effectiveness in improving student understanding. The Research and Development (R&D) method utilizing the ADDIE model was applied to 32 eleventh-grade students at a Vocational High School in Pasuruan, East Java. Data were collected through expert validation sheets, response questionnaires, and learning outcomes tests. The results showed that the module was highly feasible (material expert 80%, media expert 82%) and highly practical (85%). The effectiveness test using N-Gain obtained a score of 0.4 (medium category), indicating an improvement in student understanding. Therefore, the Tax Administration learning module integrated with the latest tax regulations is considered feasible, practical, and effective as a learning resource for improving vocational high school students' understanding of taxation.